2017
DOI: 10.1177/1079063217697132
|View full text |Cite
|
Sign up to set email alerts
|

“It’s Not Something I Chose You Know”: Making Sense of Pedophiles’ Sexual Interest in Children and the Impact on Their Psychosexual Identity

Abstract: Sexual interest in children is one of the most strongly predictive of the known risk factors for sexual reconviction. It is an important aspect of risk assessment to identify the presence of such interest, and an important task for treatment providers to address such a sexual interest where it is present. It has been argued that understanding pedophiles' deviant sexual interest in children can enhance risk assessment, management, and treatment planning. This research study aims to explore the phenomenology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 64 publications
2
21
0
1
Order By: Relevance
“…The triangulation of these two methods, therefore, increases the understanding of the phenomenon explored in this paper, providing a deeper analysis than one method alone could provide (Howitt, 2010). Indeed, the triangulation of IPA with the repertory grid technique is growing in popularity as a method of rigorous exploration of participants' meaning making (Blagden, Mann, Webster, Lee, & Williams, 2017;Turpin, Dallos, Owen, & Thomas, 2009;Yorke & Dallos, 2015). In addition, Blagden, Winder, Gregson, and Thorne (2014) have demonstrated the successful synthesis of these methods, when used in a forensic setting, with those who have been convicted of sexual offences as participants.…”
Section: Analysis Processmentioning
confidence: 99%
“…The triangulation of these two methods, therefore, increases the understanding of the phenomenon explored in this paper, providing a deeper analysis than one method alone could provide (Howitt, 2010). Indeed, the triangulation of IPA with the repertory grid technique is growing in popularity as a method of rigorous exploration of participants' meaning making (Blagden, Mann, Webster, Lee, & Williams, 2017;Turpin, Dallos, Owen, & Thomas, 2009;Yorke & Dallos, 2015). In addition, Blagden, Winder, Gregson, and Thorne (2014) have demonstrated the successful synthesis of these methods, when used in a forensic setting, with those who have been convicted of sexual offences as participants.…”
Section: Analysis Processmentioning
confidence: 99%
“…The common principle across multiple definitions of pedophilia is that it constitutes a stable sexual preference, independent of arousability/intensity of sexual feeling or gender preference (Blagden, Mann, Williams & Lee, 2018;Seto, 2012). Ahlers and Schaefer (2010) proposed that human sexual preferences should be described using three independent dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…From a wellbeing perspective, people with sexual interests in children have reported that professionals working with them appear to focus more on risk reduction (e.g., controlling sexual urges), despite them preferring to be supported in relation to the more general psychological wellbeing issues mentioned above (B4U-ACT, 2011). This in turn leads many people with pedophilic sexual interests to be unwilling to come forward to access mental health support because of doubts over whether those professionals offering such services will act in non-judgmental ways (B4U-ACT, 2011; Blagden et al, 2018). Indeed, evidence suggests that the stigma experienced by those who have a dominant sexual interest in children impairs help-seeking behaviors due to both perceived and anticipated rejection (Goode, 2010;Blagden et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of the initial literature review, was to learn about the phenomenon of interest and to identify a gap in what is known about it, but the literature is not subsequently used to inform data collection in a rigid way (Smith, 1999;Smith, Flowers and Larkin, 2009). IPA has previously been used to understand the experiences of men serving a custodial sentence for a sexual offence but who are maintaining their innocence (Blagden, Winder, Thorne & Gregson, 2011), adult males who have committed sexual offences against elderly female victims (Murphy & Winder, 2016), men who have downloaded sexually abusive images of children (Winder & Gough, 2010), male paedophiles who have committed child sexual offences (Blagden, Mann, Webster, Lee & Williams, 2017) and male prisoners who have participated in peer support schemes (Perring & Blagden, 2014).…”
Section: Introductionmentioning
confidence: 99%